Neurocysticercosis: Current Perspectives on Diagnosis and Management - Butala, Caitlin; Brook, T. M.; Majekodunmi, Ayodele O.; Welburn, Susan Christina (Frontiers in Veterinary Science, 2021)
Cysticercosis and neurocysticercosis (NCC) are a major global health problem, with NCC being a major cause of epilepsy. World Health Organization (WHO) reports an estimated 2.5-8.3 million cases annually with a DALY burden of 2.8 million. Much of the world population resides in low- and middle-income countries endemic for pork tapeworm; humans acquire Taenia solium infection from eating undercooked pork containing live cysts; the immature worm develops in the intestine and sheds eggs, expelled in human faeces. These infect humans and pigs when consumed directly in water or food. Once ingested, the larvae migrate within the body to form cysts. Pigs can harbour thousands of cysts. In humans the larvae can migrate to the central nervous system causing neurocysticercosis (NCC). This review examines recent developments for NCC diagnosis, prevention and control. Diagnosis of NCC is complex, most accurate using neuroimaging methodologies, unavailable in many areas in which the disease is endemic. Prevention of infection depends on communication and behaviour change, underpinned by control measures, including effective vaccination and deworming for pigs supported by meat inspection. With no vaccine available for humans, drug treatment with albendazole and praziquantel, widely used as part of Mass Drug administration deworming programmes underpin control efforts for these Neglected Tropical Diseases (NTD) in humans. Against a backdrop of large investments in de-worming for NTDs in humans, the lack of advocacy to support prioritization of vaccination of pigs is of concern if cysticercosis and NCC are to be eliminated. It is important to view neglected zoonotic diseases from a One Health perspective and anthelmintic resistance is widespread among livestock, with waning drug efficacy an emerging